Cluster development plan framework - Nezakati, Hossein *; Tatabaei, Seyed Mahameddin (University Putra Malaysia Press, 2009)
From the second half of 20th century different development model was created. Today development model base on small and medium size enterprises1 has become the centre of several countries consideration. In multifarious articles different model was discussed. The two important development models are as follow: 1- Development model base on large enterprise 2- Development model base on strategic cooperation of small and medium size enterprises In this article the two development models are described and the Iran industrial situation is analyzed as well, than the academic literature is reviewed in order to select the best matching development model for Iranian industries. The result of Iran industrial analyses indicates that SMEs are majority of industrial structure of the country and they are geographically distributed. Therefore the main policies of the country should focused on the SMEs and because there is a lack of large enterprises in the country therefore the model for development should be concentrated on strategic cooperation of SMEs while other information specify that cluster are the most suitable form of SMEs development. In this article based on the two main facts – academic literature and Iran industries condition- a development framework is recommended.